New plate kinematic model and tectono-stratigraphic history of the East African and West Madagascan Margins - Tuck-Martin, Amy; Adam, Jürgen; Eagles, Graeme (Basin Research, 2018)
The continental margins of East Africa and West Madagascar are a frontier for hydrocarbon exploration. However, the links between the regional tectonic history of sedimentary basins and margin evolution are relatively poorly understood. We use a plate kinematic model built by joint inversion of seafloor spreading data as a starting point to analyse the evolution of conjugate margin segments and corre- sponding sedimentary basins. By correlating megasequences in the basins to the plate model we produce a margin-scale tectonostratigraphic framework comprising four phases of tectonic development. During Phase 1 (183–133 Ma) Madagascar/India/Antarctica separated from Africa, first by rifting and later, after breakup (at ca. 170–165 Ma), by seafloor spreading in the West Somali and Mozambique basins and dextral strike-slip movement on the Davie Fracture Zone. Mixed continental/marine syn-rift megasequences were deposited in rift basins followed by shallow-marine early postrift sequences. In Phase 2 (133–89 Ma) spreading ceased in the West Somali basin and Madagascar became fixed to the African plate. However, spreading continued between the African and Antarctic plates and deposition of the early postrift megasequence continued. The onset of spreading on the Mascarene Ridge separated India from Madagascar in Phase 3 (89– 60 Ma). Phase 3 was characterized by the onset of deposition of the late postrift megasequence with continued deep marine sedimentation. At the onset of Phase 4 (60 Ma onward) spreading on the Mascarene ridge ceased and the Carlsberg Ridge propagated south to form the Central Indian Ridge, separating India from the Seychelles and the Mascarene Plateau. Late postrift deposition continued until a major unconformity linked to the development of the East African Rift System marked the change to deposition of the modern margin megasequence.